THE DYNAMICS OF IN VITRO DEGRADATION OF NON-WOVEN POLYLACTIDE MATRICES IN MODEL BIOLOGICAL LIQUID - I. A. Khlusov; K. V. Zaitsev; O. B. Zhukova; A. A. Gostyukhina; N. G. Abdulkina; A. A. Zaitsev; I. V. Kulagina; S. I. Tverdokhlebov; E. N. Bolbasov; K. S. Stankevich (Бюллетень сибирской медицины)
The weekly in vitro degradation of fibrous-porous non-woven polylactide scaffolds made by aerodynamic formation in a turbulent gas flow has been studied with 37 °С in model RPMI-1640 medium imitated body fluid of organism. Lactate monomers released into solution exponentially and reached slowly a maximum value the end of the observation (5th week of dissolution). At the same time, reducing the concentrations of calcium and inorganic phosphorus ions in solutions contacted with tested samples (10×10×1 mm2) testified about chemical elements adsorption on artificial material. Ions exchange with biological fluids may be a basis of regulated bioactivity of fibrous-porous non-woven biodegradable material in application to intercellular matrix bioengineering for regenerative medicine